The effect of age on electroencephalogram measures of anesthesia hypnosis: A comparison of BIS, Alpha Power, Lempel-Ziv complexity and permutation entropy during propofol induction - Biggs, Daniela; Boncompte, Gonzalo; Pedemonte, Juan C.; Fuentes, Carlos; Cortinez, Luis I. (Frontiers in Aging Neuroscience, 2022)
Background: Improving anesthesia administration for elderly population is of particular importance because they undergo considerably more surgical procedures and are at the most risk of suffering from anesthesia-related complications. Intraoperative brain monitors (EEG) have proved useful in the general population, however, in elderly subjects this is contentious. Probably because these monitors do not account for the natural differences in EEG signals between young and older patients. In this study we attempted to systematically characterize the age-dependence of different EEG measures of anesthesia hypnosis. Methods: We recorded EEG from 30 patients with a wide age range (19 – 99 years old) and analyzed four different proposed indexes of depth of hypnosis before, during and after loss of behavioral response due to slow propofol infusion during anesthetic induction. We analyzed BIS, Alpha Power and two entropy-related EEG measures, Lempel-Ziv complexity (LZc) and Permutation Entropy (PE) using mixed-effect ANOVAs. We evaluated their possible age-biases and their trajectories during propofol induction. Results: All measures were dependent on anesthesia stages. BIS, LZc and PE presented lower values at increasing anesthetic dosage. Inversely, Alpha power increased with increasing propofol at low doses, however this relation was reversed at greater effect-site propofol concentrations. Significant group differences between elderly patients (> 65 years) and young patients were observed for BIS, Alpha power and LZc, but not for PE. Conclusions: BIS, Alpha power and LZc show important age-related biases during slow propofol induction. These should be considered when interpreting and designing EEG monitors for clinical settings. Interestingly, PE did not present significant age differences, which makes it a promising candidate as an age-independent measure of hypnotic depth to be used in future monitor development